2013
DOI: 10.1155/2013/965282
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Coordinated Design of Multiple Damping Controllers Based on PSS and UPFC Device to Improve Dynamic Stability in the Power System

Abstract: Unified Power Flow Controller (UPFC) device is applied to control power flow in transmission lines. Supplementary damping controller can be installed on any control channel of the UPFC inputs to implement the task of Power Oscillation Damping (POD) controller. In this paper, we have presented the simultaneous coordinated design of the multiple damping controllers between Power System Stabilizer (PSS) and UPFC-based POD or between different multiple UPFC-based POD controllers without PSS in a singlemachine infi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…The new weight parameter w new is defined by ( 9) We have observed that the proposed new weight decreases and oscillates simultaneously for total iteration, whereas the conventional weight decreases monotonously from w max to w min [7] (Fig. 5).…”
Section: Chaotic Particle Swarm Optimization (Cpso)mentioning
confidence: 98%
“…The new weight parameter w new is defined by ( 9) We have observed that the proposed new weight decreases and oscillates simultaneously for total iteration, whereas the conventional weight decreases monotonously from w max to w min [7] (Fig. 5).…”
Section: Chaotic Particle Swarm Optimization (Cpso)mentioning
confidence: 98%
“…The model of linear dynamic by linearization of non−linear model for the operating condition. Figure 1 illustrates the linearized model of the power system as given by [16]: The construction of the matrices A and B are:…”
Section: Linearized Form Of Smib With Upfcmentioning
confidence: 99%
“…(4) Power oscillation incidence detection: judge whether the power oscillation amplitude of the fifth cycle is larger than 50 MW or not for any 500 kV tie line and record the oscillation curve for the oscillation property classification. buses at the power grid using the trained SVM model in procedure (3). As for the recognized result of the oscillation curves, 1 represents the negative damping oscillation and −1 represents the forced oscillation.…”
Section: Procedures Of the Oscillation Property Classificationmentioning
confidence: 99%
“…With the interconnection of large-scale power grids via high voltage long distance transmission lines, coupling between synchronous generators becomes weaker which leads to poor or negative damping ratio of power systems [1,2]. Power oscillation has become a major problem threatening the security of large-scale interconnected power systems [3,4]. In order to safely operate the power system, monitoring classification and suppression of the electric power oscillations in power grids has captured exponentially increasing attention in power engineering community in the past decade.…”
Section: Introductionmentioning
confidence: 99%